2020
DOI: 10.1177/2057158520941753
|View full text |Cite
|
Sign up to set email alerts
|

Registered nurses’ experiences of assessing patients with mental illness in emergency care: A qualitative descriptive study

Abstract: Patients with mental illness are exposed and experience themselves as not being taken seriously in emergency care. Registered nurses need to assess patients with mental illness from a holistic perspective comprising both a physical and an existential dimension. The aim of the study was to describe registered nurses’ (RNs) experiences of assessing patients with mental illness in emergency care. Twenty-eight RNs in prehospital and in-hospital emergency care were individually interviewed. The interviews were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 41 publications
0
17
0
8
Order By: Relevance
“…In a stressful situation, the condition needs to be categorized and the nurse has to decide whether the patient is suffering from a physical or mental illness. Holmberg et al [ 8 ] state that lack of time to care for the patient may cause nurses to question their responsibility for caring for the patient. The nurses complained that the information they received before the assignment did not always correspond to what they encountered on arrival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a stressful situation, the condition needs to be categorized and the nurse has to decide whether the patient is suffering from a physical or mental illness. Holmberg et al [ 8 ] state that lack of time to care for the patient may cause nurses to question their responsibility for caring for the patient. The nurses complained that the information they received before the assignment did not always correspond to what they encountered on arrival.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research has identified the complexity of assessing patients with mental illness in emergency care. It has also shown that nurses find such patients less interesting than patients with emergency somatic conditions [ 8 ]. Nurses were also found to need increased knowledge to be able to make the required assessments [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study does not examine the ambulance nurses’ attitudes regarding mental illness, but in both Swedish and foreign contexts it has been described that biomedical conditions and diagnosis are more natural to work with. One reason that can be mentioned may be the stigma that exists in society, of which nurses are a part, around mental illness [ 18 , 26 , 27 ]. Thoroughly defining a professional competence is thus complex because it can be seen as consisting of several separate specific knowledge areas required within a professional specialty [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research on GEC staffs' experiences of caring for people with mental ill health is limited (Koning et al 2018;Ryan et al 2021). However, GEC staff often report their lack of knowledge and training as a major barrier to providing appropriate care for people with mental ill health (Chapman & Martin 2014;Holmberg et al 2020;Jelinek et al 2013;Marynowski-Traczyk & Broadbent 2011;Plant & White 2013;Weiland et al 2011). The physical environment of the ED and short interactions due to time pressures further challenge the ability of GEC staff to meet patients' emotional needs (Broadbent et al 2014;Marynowski-Traczyk & Broadbent 2011;Weiland et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…2013), they still must make advanced assessments, including both physical and existential dimensions (Holmberg et al . 2020).…”
Section: Introductionmentioning
confidence: 99%